2015
DOI: 10.1002/poc.3477
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐catalyzed cyclization of 2‐alkynyl‐N‐ethanoyl anilines to indoles: synthesis, structural, spectroscopic, and mechanistic study

Abstract: This study reports a facial regio‐selective synthesis of 2‐alkyl‐N‐ethanoyl indoles from substituted‐N‐ethanoyl anilines employing palladium (II) chloride, which acts as a cyclization catalyst. The mechanistic trait of palladium‐based cyclization is also explored by employing density functional theory. In a two‐step mechanism, the palladium, which attaches to the ethylene carbons, promotes the proton transfer and cyclization. The gas‐phase barrier height of the first transition state is 37 kcal/mol, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 60 publications
(84 reference statements)
0
17
0
Order By: Relevance
“…Table Energy values of frontier orbitals are represented in Table 2 for all the compounds along with the two widely used chemical descriptors parameter, hardness and softness. Compound (9) showed the lowest HOMO-LUMO energy gap, hardness, and highest softness which revealed the molecule has more reactivity than other derivatives, according to Pearson et al [11][12]. In Figure 4 the LUMO plot of the compound (9) showed that the electron was localized at the modified acylating group regions only, while the HOMO plot showed that the electron was localized on the upper part of the thymine ring.…”
Section: Frontier Molecular Orbitals Analysismentioning
confidence: 83%
See 1 more Smart Citation
“…Table Energy values of frontier orbitals are represented in Table 2 for all the compounds along with the two widely used chemical descriptors parameter, hardness and softness. Compound (9) showed the lowest HOMO-LUMO energy gap, hardness, and highest softness which revealed the molecule has more reactivity than other derivatives, according to Pearson et al [11][12]. In Figure 4 the LUMO plot of the compound (9) showed that the electron was localized at the modified acylating group regions only, while the HOMO plot showed that the electron was localized on the upper part of the thymine ring.…”
Section: Frontier Molecular Orbitals Analysismentioning
confidence: 83%
“…The new analogues of thymidine used in this study were designated according to the reactions scheme. Thymidine (1) and its derivatives (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) were designated and optimized in the quantum mechanical method and Figure 2 shows the optimized structure of thymidine derivatives.…”
Section: Strategies and Optimization Of Designed Thymidine Analoguesmentioning
confidence: 99%
“…Among all the modified drugs, the lowest HOMO-LUMO gap has been observed for D9. The lowest HOMO-LUMO gap indicates that the molecule is more chemically reactive [ 54 ]. Pearson found that the HOMO-LUMO gap has a relation to the chemical hardness and softness of a molecule [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The difference in HOMO and LUMO energy is called gap energy and gap energy corresponds to the electronic excitation energy. The compound that has the greater orbital gap energy, tends to be energetically unfavourable to undergo a chemical reaction and vice versa [53,101,102]. Moreover, gap energy also has correlation with the hardness and softness properties of a molecule [103].…”
Section: Discussionmentioning
confidence: 99%